Skrifter udgivet af Grundtvig-Selskabet - Lundgreen-Nielsen, Flemming; Bradley, S. A. J.; Pedersen, Kim Arne; Schjørring, Jens Holger (Grundtvig-Studier, 2004)
Works published by the Grundtvig Society